Resistance to fracture of direct restorations with cuspal coverage in upper endodontically treated bicuspids (Pesquisa Odontológica Brasileira, 2001)
Endodontically treated teeth are considered more susceptible to fracture because of the loss of tooth structure. The aim of this study was to evaluate the increase of resistance to fracture of upper bicuspids that underwent endodontic access and were restored with composite resin, with cuspal coverage. Forty extracted human maxillary premolars were divided in 4 groups: I - intact teeth; II - teeth with endodontic access and MOD preparation, restored with composite resin, without cuspal coverage; III - teeth with endodontic access, MOD preparation and occlusal reduction, restored with composite resin, with cuspal coverage; IV - teeth with endodontic access and MOD preparation, without any restoration. The test specimens were submitted to compression test up to their fracture. The test of Tukey and the ANOVA analysis were used to compare and test the results. The teeth from group III (with cuspal coverage) presented with significantly greater resistance to fracture, when compared with those from groups II (restored without cuspal coverage) and IV (not restored). The composite restoration with cuspal coverage can be considered an alternative for endodontically treated premolars.